Novel decision aid model for green supplier selection based on extended EDAS approach under pythagorean fuzzy Z-numbers - Ashraf, Shahzaib; Abbasi, Shahzad Noor; Naeem, Muhammad; Eldin, Sayed M. (Frontiers in Environmental Science, 2023)
The main objective of this study is to identify the green suppliers that would most effectively assist manufacturing producers in implementing green manufacturing production while including uncertainty and reliability in their decision-making. For this, firstly, we justify and manifest the idea of Pythagorean Fuzzy Z-numbers (PyFZNs). It has significant implications for improving the effectiveness of decision-making processes in several theories of uncertainty. It can more flexibly explain real-world data and human cognition due to its capacity to express both imprecise and reliable information. Thus, it is a more accurate mathematical tool for addressing accuracy and uncertainty. Secondly, we defined the Pythagorean fuzzy Z-number arithmetic aggregation operators and geometric aggregation operators. Thirdly, based on the proposed operators and EDAS (evaluation based on distance from the average solution) approach, a fast decision model is designed to deal with the issue of multi-criteria decision-making. Finally, using PyFZN data, we also provide a numerical example to demonstrate the usability of the newly created multicriteria decision-making (MDM) approach. Moreover, a case study also proves its efficacy.